The Use of Emerging Technologies as a Didactic Strategy in the Process of Communication and Administrative Writing - Agüero Flores, Alejandra (2022)
This research was carried out in the course Curricular Integration of Emerging Technologies from the master’s degree in Education with Emphasis in University Pedagogy of the School of Educology of the Universidad Nacional de Costa Rica, in which a proposal was made for the course of Communication and Administrative Writing, whose main topic was the teaching of the commercial letter, which is one of the most used documentary types in the office. This proposal promotes the use of emerging technologies, to take full advantage of existing and commonly used tools such as mobile phones,computers, and tablets, as well as video conferencing applications such as Zoom, Teams, Google Meet, Hangouts, WhatsApp, among others, that allowinteraction between professors and students, in order to teach the course remotely, according to the needs of the students and the situation faced bythe country with the COVID-19 pandemic; for this reason, an innovative and creative pedagogical mediation was sought. Finally, this research takes the experiences of students and professors, to identify if the techniques, tools, and resources used, achieved the objective oflearning in a dynamic way, how to prepare commercial letters.